1993
DOI: 10.1016/0735-1097(93)90255-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of coronary conductance and resistance vessel reactivity in response to nitroglycerin, ergonovine and adenosine: In vivo studies with simultaneous intravascular two-dimensional and Doppler ultrasound

Abstract: This study demonstrates that nitroglycerin and ergonovine predominantly influence coronary conductance arteries whereas adenosine mainly dilates coronary resistance vessels. These findings also demonstrate that the combined use of a two-dimensional and a Doppler ultrasound transducer within one catheter assembly can provide information on the differential effects of vasoactive agents on the epicardial and microvascular coronary circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(35 citation statements)
references
References 42 publications
0
33
0
2
Order By: Relevance
“…However, nitrates also affect resistance vessels Ͼ100 m in the microcirculation (10), especially in the early transition period before compensatory action by autoregulatory control. A 50% increase in coronary flow has been reported 2 min after a 0.2 mg bolus of nitroglycerin (22). It is therefore not unlikely that the 1 mg dose of isosorbide dinitrate induced a transient decline in microvascular resistance during the 1-min measurement period.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, nitrates also affect resistance vessels Ͼ100 m in the microcirculation (10), especially in the early transition period before compensatory action by autoregulatory control. A 50% increase in coronary flow has been reported 2 min after a 0.2 mg bolus of nitroglycerin (22). It is therefore not unlikely that the 1 mg dose of isosorbide dinitrate induced a transient decline in microvascular resistance during the 1-min measurement period.…”
Section: Discussionmentioning
confidence: 98%
“…The first intervention was the administration of adenosine, which dilates coronary resistance vessels in the microcirculation and not the larger coronary arteries (10,22). This intervention should therefore have no direct effect on local wave speed measured in an epicardial conductance vessel.…”
mentioning
confidence: 99%
“…24 Nitric oxide will dilate coronary artery size even at the segments of impaired endothelial function. 24 Sudhir et al 25 demonstrated that nitroglycerin predominantly influences coronary conductance arteries and has considerable effect on increased cross-sectional area with minimal effect on coronary resistance. This is not consistent with our finding which showed that nitroglycerin had a similar effect on conduit (cross-section area increased by 28%) and resistance vessels (vascular resistance decreased by 21%).…”
Section: Effect Of Nitroglycerinmentioning
confidence: 99%
“…Furthermore, Adenosine acts mainly at the level of the microcirculation and does not alter significantly the diameter of the coronary artery. Adenosine is administered intravenously (0.140 mg/kg/min) for 5 minutes (Lapeyre AC III et al, 2004, Sudhir K et al, 1993, Verani MS, 1991, Wilson R et al, 1990. The normal range of CFVR for both men and women is ≥ 2.7.…”
Section: Coronary Flow Reservementioning
confidence: 99%